Reforming School Discipline: Responses by School District Leadership to Revised State Guidelines for Student Codes of Conduct. (April 2021) - Curran, F. Chris; Finch, Maida A.
Purpose: Over the past decade, increasing attention to the negative impacts of exclusionary discipline and disparities therein has led many state educational leaders to enact school discipline reforms. This study examined the response by school district leadership to a state's revision of guidelines for student codes of conduct.Data: This study leveraged longitudinal data on school district codes of conduct from the 2013–2014 to 2015–2016 school years across the state of Maryland. Codes of conduct were coded in an iterative fashion according to a common set of infraction–response combinations.Research Design: Using a pre–post analytic design, this study examined changes in districts' codified infractions, responses to infractions, and the overall tier of response. Furthermore, the study compared alignment between state guidelines and district codes of conduct while exploring variation in codified discipline across districts.Findings: Findings suggest that leaders in districts increased the number of response options available for most types of infractions, with the largest increases occurring for more serious infractions. While these increases tended to be driven by increases in the codification of less exclusionary responses, there were nevertheless sizeable increases in the availability of in-school suspension and removal/intervention. In almost all cases, school districts reported distributions of response options that were at a higher tier level than that recommended by the state.Conclusions: Findings are discussed in the context of current efforts to reform school discipline and the implications of such reform for implementation by district and school leadership.